A series of methods for investigating the effect of a flow improver on the asphaltene and resin of crude oil. (15th November 2019) - Quan, Hongping; Li, Pengfei; Duan, Wenmeng; Chen, Liao; Xing, Langman
Abstract: With the increasing of oil demand and the decreasing of conventional crude oil production, unconventional crude oil is gaining interest. A flow improver (FI) was synthesized and designed a series of methods for investigating the effect of the flow improver on the asphaltene and resin of two unconventional crude oil samples. Changes in the morphology of the solid samples, as determined by scanning electron microscopy. n -Heptane and alcohol were selected as poor solvents for asphaltene and resin, respectively, to prepare solution samples of different concentrations. The precipitation tendency was judged according to the color change of the solution. Fluorescence microscopy was used to observe the changes in the aggregation morphology of the solution samples before and after FI addition. Solid samples and solution samples were tested by XRD and UV spectrophotometry, respectively. The results consistently showed that the effect of FI on resin was better than that on asphaltene. The effect of asphaltene and resin on the viscosity of crude oil was investigated through the series of studies. Highlights: Designed methods to investigate the effect of flow improver on asphaltene/resin. The effect of FI on resin was analyzed. The alcohol was selected as the poor solution of resin.